Pendidikan Sains Berbasis Agama untuk Membangun Hidup Sehat - Abu Darda (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
Term of halalan in the religion means allowed, whereas in the sciencemeans healthy. Conservative aspect of faith-based on science educationprovide an explanation of the blood from the values of religion and science.From the religious point, blood (ad-dam) was haram consumed, while scienceexplains that the consumption of blood is harmful to health. The scientificinformation can help us understand the secret dimension (hikmah)prohibition of the blood, that the Lord of Maintaining His servants. Role ofscience education that based on religion is warning people to choose whichis lawful and what is not lawful; which thoyyib and which is not thoyyib.Eating liver and spleen in the perspective of religion is lawful, whereasfrom the perspective of science, it is allowed in limited quantities. Childrenshould consume these types innard, but parents should not. Finally, therole of creative-innovative science education based on religion is warningpeople to make food based on scientific and religious-minded as theembodiment of the values halalan-thayyiban in civilization. This articleaims to explore the role of science education based on religion in increasingawareness of scientific and religious, particularly those associated withblood in personal and social life. Through the methods of literature authorsconcluded the important of optimize the role of conservative criticismevaluative,and creative-innovative science education based on religion toimprove people’s attitudes and behaviors with the blood according to thevalue of halalan-thayyiban.